Hermeneutika Double Movement Fazlur Rahman: Mewujudkan Hukum Islam yang Lebih Eksistensialis - Mohamad Yufidz Anwar Ibrohim; Nur Muhammad (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The method of interpretation of classical scholars is still too "stiff" when it comes to dialogue with today's contemporary problems. Therefore, there is a need for a new epistemology that is in accordance with the development of the social situation, culture, science and human civilization. This article attempts to analyze Fazlur Rahman's thoughts on his double movement hermeneutics. This library research found that Fazlur Rahman appeared as an answer to the dynamics of Al-Qur'an interpretation. The originality of the formulated interpretation method rests on the disciplines of philosophy, social sciences and humanities. The double movement hermeneutic method refers to a process that involves two points of view, namely today's problems leading to the revelation of the Qur'an and from the time of the Qur'an returning to today's problems. This method not only contributes to the development of methods of interpreting the al-Qur’an, but also influences the process of ijtihad in order to establish Islamic laws that are more existential.